WHITE LIES AS A SPEECH ACT IN RICHARD LINKLATER’S TRILOGY FILM ‘BEFORE’ - Harmin, Irma; Halim, Abdul (ELITERATE : Journal of English Linguistics and Literature Studies, 2024)
This research aimed to find out the differences between real lies and white lies, white lies uttered in films related to speech acts, and the effects of a white lie on a relationship between the speaker and the listener using a pragmatic approach. This research method used descriptive qualitative, namely the process of processing data by selecting and simplifying the data, then analyzing and compiling it systematically so that conclusions can be drawn. The sources were from the Before trilogy films, namely Before Sunrise, Before Sunset, and Before Midnight. The white lies spoken throughout the entire three films were varied from the innocent one night stand journey Celine and Jesse had in the first film Before Sunrise, then the short encounter yet so meaningful they had in Paris in the second film Before Sunset, and last but not least, Before Midnight, the third film making it as a complete trilogy where Celine and Jesse already married and a parent to twin girls, additionally continued their bittersweet discussion about love and life to remain as a loving, married couple. The results of this study showed twenty-five white lies as speech acts recorded in the three films. Three out of five types of speech acts appeared in the films, specifically assertive, commissive, and expressive speech acts. Eleven assertive speech act data, five commissive speech act data, and nine expressive speech act data were found in the trilogy films in the context of white lying. The results of the research also showed that people can lie when uttering speech acts such as promising, offering, convincing, and refusing. The results also indicated that white lie has always been an inevitable aspect of daily life conversation.